«Your loyal subject S. R.»: on the only letter of S. A. Rachinsky to Emperor Nicholas II - Petr Pantuev; Fedor Otto (Vestnik Pravoslavnogo Svi͡a︡to-Tikhonovskogo gumanitarnogo universiteta. II, Istorii͡a︡, istorii͡a︡ Russkoĭ pravoslavnoĭ t͡s︡erkvi, 2024)
Sergey Rachinsky, a professor tof the Moscow University, an educator and the founder of the school in Tatevo, Tver Oblast, and also the founder of 20 schools near Tatevo, was a close friend and interlocutor of Konstantin Pobedonostsev, Sergey Smolensky, Vasily Rozanov, Leo Tolstoy and many other famous contemporaries. On 14 May 1899, Emperor Nickolas II signed an Imperial rescript addressed to Rachinsky, thanking him for his work in public education. This article focuses on the circumstances of the appearance of the rescript. On the basis of archival documents, the author of the article shows that there was a specific reason for the appearance of the rescript. Rachinsky was concerned about two schools founded by himself, that they were deprived of the status of a parish school and also were deprived of funding by local authorities. His close friend, the chief Procurator of the Synod K.P. Pobedonostsev, decided to help his friend and wrote the text of the rescript, which was presented to Emperor Nickolas II for signature. Rachinsky also wrote a letter to the Emperor, following the advice of Konstantin Pobedonostsev, showing that he was a committed monarchist and the letter to the emperor was a sincere display of his fillings.